2018
DOI: 10.1080/0142159x.2018.1472372
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative use of virtual patients after a lecture enhances learning with minimal investment of cognitive load

Abstract: Collaborative use of VPs after a lecture is the most efficient instructional method, of those tested, as it leads to better learning and transfer combined with lower cognitive load, when compared with independent use of VPs, either before or after the lecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Although the study was conducted in SA, it is safe to assume that similar factors operate in schools with the same setting in various parts of the world. ere is increase in dissatisfaction with traditional curricula as reflected by several studies conducted in SA and investigating the introduction of contemporary teaching and assessment tools [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Although the study was conducted in SA, it is safe to assume that similar factors operate in schools with the same setting in various parts of the world. ere is increase in dissatisfaction with traditional curricula as reflected by several studies conducted in SA and investigating the introduction of contemporary teaching and assessment tools [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The virtual space gives the learners the chances of communication, severe involvement, scripted immersive experiences, imitations, playacting and constructivist education (Kim and Park, 2020; Wiecha et al , 2010). So, it's been shown that technological advancements had allowed novel techniques for offering content and transformed it into a more thorough medium of the content offering (Marei et al , 2019). We can describe the amplified flexibility as access broadening to many programs up to the known official postgraduate credentials from several foundations and the huge electronic courses (Iskander, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that collaborative learning and social interaction through elaboration with peer discussion can reduce intrinsic and extraneous cognitive load [34]. Also, it was suggested that during collaborative VPs, students could link new information and new knowledge with the old or prior knowledge (schemata) or even build new schemata in a better way with less intrinsic and extraneous cognitive loads [5,[23][24][25]35]. These studies attributed the efficiency of collaborative learning to several factors including a) the instructional design of VPs which containing simulated clinical scenario similar to the real practice, b) social discussion and elaboration with the peers and c) continuous feedback given to the student during the collaborative VPs session by the instructor.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that VPs can offer curricula that are rich in authentic activities and full of a variety of problems that can be a very effective tool for knowledge acquisition and retention [ 3 , 5 , 6 ]. In addition, several studies focused on the importance and the effect of the sequence of VPs before or after other learning instructional methods to achieve maximum benefit for the learner.…”
Section: Introductionmentioning
confidence: 99%